(untitled) (Academicia Globe: Inderscience Research, 2021)
The study of the pathogenetic mechanisms of the development of depigmentation and the search for adequate combined methods of treating patients with vitiligo is one of the most urgent areas of modern dermatology; the study was carried out on the basis of the regional dermatovenerological dispensary. The study was conducted between 2019 and 2020. We conducted a randomized comparative study of seventeen male patients with extensive depigmented spots on the face, which were snow-white when viewed with a Wooden Lamp, with a clinical diagnosis of vitiligo, and they were examined at the regional dermatological dispensary in the city of Samarkand. These patients suffered from chronic vitiligo that remained stable for 3-10 years.